Impact of alcohol and drug use on bicycle and electric scooter injuries and hospital admissions in the United States. (January 2023) - Namiri, Nikan K; Lee, Austin W; Amend, Gregory M; Vargo, Jason; Breyer, Benjamin N
Introduction: Bicycles and electric scooters (e-scooters) are convenient and accessible means of transportation. Participant safety is contingent on available infrastructure and safe riding practices including not riding while intoxicated. Understanding national prevalence and injury characteristics of bicycle and e-scooter riders who ride while intoxicated may promote awareness campaigns for safe riding practices and decrease morbidity. Methods: The National Electronic Injury Surveillance System (NEISS) provides national estimates of injuries that present to emergency departments across the United States. We obtained case information on admitting status, body part injured, diagnosis of injury, age, sex, alcohol usage, and drug usage. We then queried NEISS for injuries related to bicycles and e-scooters in 2019. Results: A weighted total of 270, 571 (95% confidence interval (CI): 204, 517–336, 625) bicycle injuries occurred in the United States during 2019; alcohol and drug use were associated with 7% (95% CI: 6–9) and 2% (95% CI: 2–3) of all injuries, respectively. Twenty-four percent (CI: 18–31) of alcohol- and 29% (95% CI: 20–41) of drug-related bicycle injuries resulted in hospital admissions, compared to 15% (95% CI: 12–17) of non–alcohol- and 15% (95% CI: 13–18) of non–drug-related injuries ( p < .001 and p = .002, respectively). A total of 28, 702 (95% CI: 13, 975–43, 428) e-scooter injuries occurred in 2019; alcohol and drug use were associated with 8% (95% CI: 5–12) and 1% (95% CI: 1–2) of injuries, respectively. Sixty percent (95% CI: 47–72) of alcohol-related e-scooter injuries resulted in head trauma, compared to 28% (95% CI: 24–32) of non–alcohol-related injuries ( p < .001). Conclusions: Intoxication is associated with increasingly severe injuries, hospital admissions, and head trauma in bicycle and e-scooter riders. The findings support awareness campaigns to educate riders about risky practices, improve non-auto infrastructure, and promote helmet usage.